2016
DOI: 10.1089/zeb.2015.1166
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Assessment in Zebrafish During the First Week Postfertilization

Abstract: The zebrafish (Danio rerio) is a valuable vertebrate model for human hearing disorders because of many advantages in genetics, embryology, and in vivo visualization. In this study, we investigated auditory function of zebrafish during the first week postfertilization using microphonic potential recording. Extracellular microphonic potentials were recorded from hair cells in the inner ear of wild-type AB and transgenic Et(krt4:GFP) sqet4 zebrafish at 3, 5, and 7 days postfertilization in response to 20, 50, 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 59 publications
1
44
1
Order By: Relevance
“…It is unknown whether this pathway is developed in larval zebrafish, as most studies of hearing in zebrafish have looked at juveniles or adults (Cervi, Poling, & Higgs, ; Higgs et al, ; Higgs, Souza, Wilkins, Presson, & Popper, ; Mueller, ; Wang et al, ). The few studies assessing larval hearing have used microphonic potentials to gauge responses in the ears' hair cells (Lu & DeSmidt, ; Rohmann, Tripp, Genova, & Bass, ; Yao et al, ), and this work has shown responses to tones ranging from 20 Hz to 400 Hz as early as 3 days postfertilization (dpf) (Yao et al, ). By 5–6 dpf, larvae startle to tones up to 1,000 Hz, although these responses require extremely strong stimuli (Bhandiwad, Zeddies, Raible, Rubel, & Sisneros, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether this pathway is developed in larval zebrafish, as most studies of hearing in zebrafish have looked at juveniles or adults (Cervi, Poling, & Higgs, ; Higgs et al, ; Higgs, Souza, Wilkins, Presson, & Popper, ; Mueller, ; Wang et al, ). The few studies assessing larval hearing have used microphonic potentials to gauge responses in the ears' hair cells (Lu & DeSmidt, ; Rohmann, Tripp, Genova, & Bass, ; Yao et al, ), and this work has shown responses to tones ranging from 20 Hz to 400 Hz as early as 3 days postfertilization (dpf) (Yao et al, ). By 5–6 dpf, larvae startle to tones up to 1,000 Hz, although these responses require extremely strong stimuli (Bhandiwad, Zeddies, Raible, Rubel, & Sisneros, ).…”
Section: Introductionmentioning
confidence: 99%
“…At 7 dpf, larvae were fixed in 2% paraformaldehyde solution overnight and treated with 0.5% Triton X‐100 for 2 hr to permeabilize the tissue and dissolve the otoliths. Hair cell stereocilia were then labeled with Alexa Fluor® 546‐phalloidin (1:50 dilution, Thermo Fisher Scientific, Grand Island, NY) overnight (Grati et al, ; Yao et al, ). After larvae were embedded in an anti‐fade solution on a slide, stereocilia of hair cells in the saccule were scanned and 3D reconstructed using a Nikon C1 confocal microscope, and hair cell stereociliary bundles were then quantified with Nikon NIS‐Elements imaging software (Yao et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Each fish was embedded dorsal side up on a MatTek Petri dish containing 1.8% low melting agarose and 0.045% phenol red for color visualization of the agarose. Buffered 0.009% MS‐222 commonly used for electrophysiological recordings was added to immobilize larvae (Trapani and Nicolson, ; Lu and DeSmidt, ; Ricci et al, ; Olt et al, ; Yao et al, ). The agarose covering the right dorso‐lateral side of the fish was removed with a 31.5 gauge syringe needle in order to position both a recording electrode and a stimulus probe.…”
Section: Methodsmentioning
confidence: 99%